The changing gender differences in life expectancy in Chinese cities 2005-2010. - Yan Le; Jie Ren; Jie Shen; Tong Li; Cheng-Feng Zhang (PLoS ONE, 2015)
OBJECTIVES:To analyze the gender difference in life expectancy in Chinese urban people and explore the age-specific and cause-specific contributions to the changing gender differences in life expectancy. METHODS:Data of life expectancy and mortality were obtained from "Annual statistics of public health in China." The gender difference was analyzed by decomposition method, including age-specific decomposition and cause-specific decomposition. RESULTS:Women lived much longer than men in Chinese urban areas, with remarkable gains in life expectancy since 2005, respectively. The gender difference reached a peak in 2007. Mortality difference between men and women in the 60-79 age group made the largest contributions to the gender gap in life expectancy in all 6 years. Among causes of death, cancers, circulatory diseases and respiratory diseases made the largest contributions to the gender gap. 33-38% of the gender gap were caused by cancers, among which lung cancer contributed 0.6 years of the overall gap. The contribution of cancers to the gender gap reduced over time, mostly influenced by the narrowing effect of liver cancer on gender gap. Traffic accidents and suicide were the external causes influencing the gender gap, contributing 10-16% of the overall difference. CONCLUSION:Public health efforts to reduce excess mortalities for cancers, circulatory disease, respiratory diseases, and suicide among men in particular might further narrow the gender gap in life expectancy in Chinese cities.